Resurfacing of Two Separate Digital Defects Using a Single Fascial Free Flap with Neosyndactylization - Herrera, Fernando A., Jr.; Horton, Karen M.; Brennan, Ryan; Buncke, Gregory M.; Buntic, Rudolph F. (Journal of Reconstructive Microsurgery Open, 2018)
We report a case of a 20-year-old patient who sustained a mutilating crush injury to the left-hand index and ring finger volar surface measuring 5 × 6 cm from the distal end of the proximal phalanx to the fingertips. After thorough debridement and stabilization of the skeletal injury, a radial forearm fascia only free flap measuring 6 × 7 cm was used to resurface the distal soft tissue volar defect of two adjacent fingers. Digital nerve grafting was also required, and this was done using autologous nerve graft from the lateral antebrachial cutaneous nerve. This thin fascia only flap allows for stable soft tissue coverage and provides a gliding surface for the underlying tendons. The neosyndactylized digits were safely divided at 3-month follow-up, and excellent functional and aesthetic results were achieved. The radial forearm fascia is a thin, durable, and pliable tissue that is based on the radial artery as a vascular pedicle. We consider this free fascial flap as a valuable option for coverage of multiple complex distal digit injuries using a single flap and highly recommend its use.
Keywords: free fascia flap; neosyndactyly; digital resurfacing